2013
DOI: 10.1111/acer.12148
|View full text |Cite
|
Sign up to set email alerts
|

Combining Naltrexone and Prazosin in a Single Oral Medication Decreases Alcohol Drinking More Effectively Than Does Either Drug Alone

Abstract: BACKGROUND Naltrexone (NTX) is under-utilized in clinical treatment settings because it’s efficacy is modest, it is not effective for all alcoholics and, when it is effective, a significant number of alcoholics fail to maintain initial treatment gains and subsequently relapse to heavy drinking. This has slowed acceptance of NTX by the treatment community and there is a clear need for additional treatments for alcoholism and alcohol use disorders. Given that NTX and prazosin can each reduce alcohol drinking in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
52
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 49 publications
15
52
0
Order By: Relevance
“…These two dose combinations of prazosin/naltrexone are the one example of the increased effectiveness of combination treatment on ethanol-reinforced responding that was not also observed with sucrose-reinforced responding. This is also in agreement with Froehlich and colleagues (2013a) in which 2.0 mg/kg prazosin in combination with 10 mg/kg naltrexone, administered via an oral gelatin, reduced ethanol consumption more effectively than either drug alone during one week of consecutive treatment in a free-access 2-hour, 2-bottle choice paradigm in P rats.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These two dose combinations of prazosin/naltrexone are the one example of the increased effectiveness of combination treatment on ethanol-reinforced responding that was not also observed with sucrose-reinforced responding. This is also in agreement with Froehlich and colleagues (2013a) in which 2.0 mg/kg prazosin in combination with 10 mg/kg naltrexone, administered via an oral gelatin, reduced ethanol consumption more effectively than either drug alone during one week of consecutive treatment in a free-access 2-hour, 2-bottle choice paradigm in P rats.…”
Section: Discussionsupporting
confidence: 90%
“…Recent evidence suggests that the noradrenergic system plays a key role in mediating ethanol-motivated behaviors in both alcohol-dependent and non-dependent humans and rats (Froehlich et al 2013a,b; Fox et al 2012; Gilpin and Koob 2010; Rasmussen et al 2009; Simpson et al 2009; Verplaetse et al 2011; Walker et al 2008). Prazosin, an α 1 -adrenergic antagonist, has been found to reduce ethanol drinking in home cage, limited access paradigms in P rats (Rasmussen et al 2009) and block operant responding for ethanol in dependent Wistar rats, with higher doses necessary to be effective in non-dependent animals in a fixed ratio (FR) paradigm (Walker et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiolyic agents, such as prazosin, may substitute for the anxiolytic effects of alcohol and thereby reduce motivation to drink and reduce alcohol intake. In a series of preclinical studies we have found that prazosin decreased alcohol drinking/self-administration in many experimental conditions: in rats selectively bred for high voluntary alcohol drinking during both acute (Rasmussen et al, 2009) and prolonged (Froehlich et al, 2013a) treatment; when administered alone or in combination with naltrexone (Froehlich et al, 2013b); when administered during reaccess to alcohol following periods of alcohol deprivation (Rasmussen et al, 2009); and when administered during acute alcohol withdrawal (Walker et al, 2008). In humans, prazosin has been used to treat posttraumatic stress disorder (PTSD) where it reduces hyperarousal, overall PTSD severity (Raskind et al, 2003) and, parenthetically, alcohol drinking (Raskind et al, 2009).…”
mentioning
confidence: 99%
“…Prazosin dose-dependently reduced withdrawal-induced operant self-administration of alcohol in alcohol-dependent Wistar rats (Walker, Rasmussen, Raskind, & Koob, 2008). Prazosin also suppressed voluntary alcohol drinking by rats selectively bred for alcohol preference (P line) when administered either acutely (Rasmussen, Alexander, Raskind, & Froehlich, 2009) or chronically (Froehlich, Hausauer, Federoff, Fischer, & Rasmussen, 2013; Froehlich, Hausauer, & Rasmussen, 2013). The ability of prazosin to reduce alcohol drinking has been confirmed in humans; Simpson and colleagues (2009) reported that prazosin decreased relapse alcohol drinking in treatment-seeking alcohol-dependent men.…”
Section: Introductionmentioning
confidence: 99%